Theoretical and practical notes about the extension activity Literature and Culture of Federal University of São Carlos (Olhar de Professor, 2023)
The goal of this article is presenting three literature-interarts classes based on teaching experiences as case studies. In other words, I argue in this article a theoretical-practical knowledge (BONDÍA, 2022) from teaching literature in an extension activity. Methodologically, these proposals are narratives of authentic activities converted into reflections about the teaching of literature that dialogues with other arts. In order to present them, I have based the proposal of this article on the deconstruction of the dichotomy theory and practice before, during and after each lesson taught (CANDAU, LÉLIS, 1999). That is, this text turns its methodological-theoretical attention to the meditation, theorization, and academic-scientific dissemination of knowledge coming from the teaching experience. All the qualitative data of this article were collected during the extension activity "Literature and Culture" (LeC), organized and taught by UFSCar’s students and professors at state schools of São Carlos, São Paulo.
Keywords: Extension activity. Interarts. Literature teaching.